Analisis Potensi dan Kesenjangan Penerimaan Pajak Pertambahan Nilai di Indonesia Tahun 2013 - Sugana, Rubino; Hidayat, Asrul (UI Scholars Hub, 2014)
This study is conducted to develop a model that can be used to estimate the VAT revenue potential, tax gaps, and the impact of policy changes using the Input-Output Table. The amount of VAT revenue projection generated by this model is close to the VAT revenue realization. The result of this study shows that the VAT compliance rate is only around 53%. Improving VAT compliance rate would generate a higher impact on VAT revenue as compared with raising the VAT rate. On the other hand, removing all VAT exemptions, besides increasing the administrative burden, it could also reduce VAT revenue from certain economic sectors, even though it will reduce economic distortions and avoid the need for special VAT treatment.